Sustainable protocols for leaf sample collection in In-Vitro Culture: evaluating the impact of sample bags and hydrogen peroxide pre-sterilization - Nursuria Md Setamam; Norrizah Jaafar Sidik (Penerbit Universiti Kebangsaan Malaysia, 2024)
This study investigates sustainable leaf sample collection protocols for in-vitro culture (IVC) of chili (Capsicum frutescens) and tomato (Solanum lycopersicum) leaves. The research aimed to enhance viability and reduce contamination of leaf explants by evaluating various types of sample bags and different concentrations of hydrogen peroxide (H2O2) pre-sterilization. Specifically, the study compared the effectiveness of normal sealed (NS) bags and vacuum-sealed (VS) bags, including high-action (VSH) and low-action (VSL) vacuum-sealed bags, alongside H2O2 pre-sterilization at various concentrations. Leaf samples were treated with ten different concentrations of H2O2 (5% to 50%) to assess their impact on necrosis and surface contamination over 72 hr. Results showed that higher H2O2 concentrations (above 30%) caused significant necrosis, while concentrations between 10% and 15% provided optimal pre-sterilization for both leaf types, effectively reducing contamination without excessive tissue damage. In the second phase, the research examined the influence of different sample bags on leaf explant sustainability. Vacuum-sealed bags, particularly those with low-action vacuum (VSL), significantly improved leaf longevity and minimized contaminant emergence compared to normal sealed bags. Combined with 15% H2O2 pre-sterilization, VSL bags performed best, maintaining leaf morphology and viability for extended periods. Statistical analyses confirmed the significant impact of sampling bag type and pre-sterilization on contamination levels, necrosis emergence, and leaf longevity. The findings suggest that using low-action vacuum-sealed bags (VSL) with 15% H2O2 pre-sterilization is a promising approach for sustainable leaf sample collection, enhancing the success rate of IVC by minimizing microbial contamination and preserving leaf integrity during transport. This optimized protocol offers valuable insights for researchers and practitioners in plant tissue culture and agriculture, aiming to improve the sustainability and efficiency of leaf sample collection for in-vitro applications.